Over reporting of RCH services coverage and operational problems in health management information system at the sub-center level - Verma R; Prinja S (Wolters Kluwer Medknow Publications, 2007)
Objective: To evaluate the coverage of MCH services as against reported coverage and assess the extent of usage of health information system. Study Design : Community-based cross-sectional study. Setting: Twenty sub-centers of block Lakhanmajra, district Rohtak. Participants: Four hundred mothers having children between 1-2 years age. Statistical Analysis : Simple proportions percentages. Results: The study revealed marked variation in reported and evaluated coverage of various service indicators for MCH care. TT coverage and tubectomies performed were the only notable exceptions that where reported and evaluated coverage matched largely. Distressingly, only 10% of health workers used the eligible couple and child information register for prioritizing clients and preparing the sub-center action plans. The workers did not sufficiently use the information generated through registers, records, and reports maintained at sub-centers.